Assessing the Role of Vocabulary Breadth and Depth in Reading Comprehension: A Quantitative Study of Finnish EFL Learners - Harkio, Noora (My University, 2016)
In this MA thesis, Finnish learners of English were studied in order to examine the relationship between second language vocabulary size, vocabulary depth, and reading comprehension. In addition, given the well-established connection between vocabulary size and reading comprehension, the second aim of the study was to see whether assessing vocabulary depth could add another dimension in predicting and explaining reading comprehension proficiency. Two groups were studied: the first group consisted of 39 Finnish upper secondary school students (the TOKA group) whereas the second group consisted of 19 university students of English at the University of Turku (the YLI group). Thus, comparisons were made between the results of a less advanced and a very advanced group of English learners, which was the third aim of the study. The participants in both groups filled in a background information form and took three tests: a multiple-choice reading comprehension test, a multiple-choice vocabulary size test, and a test designed to elicit information on learners’ depth of vocabulary knowledge of certain English words. The data were analysed using statistical methods. The results of the study show that the scores on the three tests were positively correlated in both study groups as well as in the two groups together. However, the correlations were higher in the TOKA group and in the two groups in total than in the YLI group. When examining the variance in reading comprehension test scores explained by vocabulary size and vocabulary depth, the figures of explained variance were again higher in the TOKA group and in the two groups in total than in the YLI group. When it comes to the results of the YLI group, vocabulary depth did not indeed seem to add any explained variance into the explanation of reading comprehension test scores. Based on the results of the study, it seems that vocabulary size and depth have a less significant role in the reading comprehension skills of more advanced learners of English. When looking at the less advanced TOKA group, on the other hand, vocabulary size and depth seem to be clear indicators of reading proficiency. In addition, the test results of the YLI group were clearly more uniform than those of the TOKA group. The variance in the test results of the TOKA group was large.